Modelo sociocultural como estrategia educativa para la prevención de consumo de tabaco en adolescentes de 15 a 17 años en la Unidad Educativa Jose Ángel Palacios - Toledo Illescas, Ana Gabriela (2018)
The consumption of tobacco in adolescents aged 15 to 17 years has caused great concern in recent times and its evident impact on the quality of life of affected individuals has served as a motivation to propose the socio-cultural model as a support to the community for the prevention of tobacco consumption in adolescents of the tenth year of the José Ángel Palacio Educational Unit. he methods that were used are located in areas: theoretical-diagnostic, design-planning, proposal and evaluation-assessment of it, therefore the scientific method was used, in addition to theoretical methods such as analytical-synthetic, inductive-logical , descriptive, hermeneutic, dialectical, phenomenological; Empirical methods such as: the AUDIT and CAGE questionnaire, which provided the measurement of tobacco consumption levels in a 76% pre-test. The social and cultural factors that influence and lead to consumption, such as family, friends and colleagues, are considered of significant value, which triggers a consumption to experiment, to be accepted or to the customs that are still deeply rooted in families. Therefore, with the activities applied to the students of the institution, the level of tobacco consumption was reduced, allowing the adolescents to understand and recognize factors that directly influence the consumption of tobacco, it was possible to decrease to 20% in said students; being able to demonstrate the effectiveness of the Sociocultural model and recommending to the entire scientific community the use in the educational field to eliminate this social problem. Therefore the consumption of tobacco by adolescents is the result of influences partner. It is recommended to incorporate prevention campaigns in the educational unit, which is linked to the socio-cultural model for the prevention of tobacco consumption, as a last place that this work is used for students who want to intervene in prevention of tobacco use ruling in the socio-cultural model.